2021
DOI: 10.1136/bmjnph-2020-000193
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin B12deficiency and B12screening trends for patients on metformin: a retrospective cohort case review

Abstract: ObjectivesOur study investigated the use of vitamin B12 testing in a large cohort of patients on metformin and assesses appropriateness and benefits of screening recommendations for vitamin B12 deficiency.DesignThis retrospective cohort study included insured adult patients who had more than 1 year of metformin use between 1 January 2010 and 1 October 2016 and who filled at least two consecutive prescriptions of metformin to establish compliance. The comparison group was not exposed to metformin. Primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A recent retrospective study conducted in a large cohort of adult patients ( n = 13489) who had received metformin for more than 1 year aimed to assess the appropriateness and benefits of screening recommendations for vitamin B12 deficiency[ 47 ]. The mean time between metformin initiation and incidence of vitamin B12 deficiency was 5.3 years.…”
Section: Metformin-induced Vitamin B12 Deficiency: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study conducted in a large cohort of adult patients ( n = 13489) who had received metformin for more than 1 year aimed to assess the appropriateness and benefits of screening recommendations for vitamin B12 deficiency[ 47 ]. The mean time between metformin initiation and incidence of vitamin B12 deficiency was 5.3 years.…”
Section: Metformin-induced Vitamin B12 Deficiency: Clinical Evidencementioning
confidence: 99%
“…These results suggest that patients who have been using metformin for more than 5 years and patients older than 65 are at increased risk for vitamin B12 deficiency. Therefore, authors concluded that screening for vitamin B12 deficiency might be considered in such populations even if they are asymptomatic for the deficiency[ 47 ].…”
Section: Metformin-induced Vitamin B12 Deficiency: Clinical Evidencementioning
confidence: 99%
“…Patients suffering from PCOS are at risk of long-term negative health hazards that are not, or only partly addressed by the usual allopathic treatments, the adherence to which is suboptimal in real-world [33]. In addition, Metformin may induce Vitamin B12 deficiency [34]. The mechanisms underlying PCOS-associated health hazards must be targeted and corrected, in order to improve the wellbeing of patients and to reduce the probability of ill-health when aging.…”
Section: Discussionmentioning
confidence: 99%
“…32 Similar results were obtained in studies from Korea, 33 Brazil 34 and the USA. 35 In addition, a nested case-control study from Hong Kong showed that for each 1-g dose of metformin that was being utilized there was a 2.88-fold (95% CI 2.15-3.87, p = 0001) increase in vitamin B12 deficiency and in those utilizing metformin for over 3 years a 2.39-fold increase (95% CI 1.46-3.91, p = 0.001). 36 Similarly, case reports have described low serum vitamin B12 levels being associated with metformin use.…”
Section: Studies Of Metformin Causing Vitamin B12 Deficiencymentioning
confidence: 99%